Reliability of a contact and non-contact simulated team game circuit - Singh, T. K. R.; Guelfi, K. J.; Landers, G.; Dawson, B.; Bishop, D. (Journal of Sports Science & Medicine, 2010)
Most team sports are characterised by repeated short maximal sprint efforts interspersed with longer periods of active recovery or rest. Although a variety of testing protocols have been devised to simulate these activity patterns under controlled conditions, a common limitation is the lack of 'body contact' to simulate the tackling efforts seen in contact sports. Therefore, the purpose of this study was to assess the reliability of a simulated team game protocol with and without 'contact'. Eleven male, team-sport athletes (mean ± SD; age 22 ± 2 yr; BMI 23.0 ± 1.7 kg·m-2) completed four separate testing trials; two 'non-contact' trials (NCON) and two 'contact' (CON) trials of a simulated game to determine the reliability of a range of team sport performance indicators including repeated 15-m sprint time, vertical jump height, heart rate response and ratings of perceived exertion (RPE). The team game protocol involved four sets of 15-min of intermittent running around a circuit replicating the movement patterns observed in team sports, either with or without simulated contact. Within-subject reliability of each performance measure was determined by expressing the typical error of measurement as the coefficient of variation, as well as determining intra-class correlations. Both CON and NCON produced reliable results for a variety of team sport performance indicators including repeated 15-m sprint time, vertical jump height, heart rate response and RPE. Repeated sprint and jump performance declined over time throughout the simulated game (p < 0.05), while heart rate and RPE increased. There was no difference in these performance measures between CON and NCON protocols. As such, these simulated game protocols provide reliable options for assessing team game performance parameters in response to training or other interventions under controlled conditions.